Family Tourist - is Different Motive, Different Choice of Tourist Activity? - Ingkadijaya, Rahmat (E-Journal of Tourism; Volume 5 Number 2 (September 2018), 2018)
Currently, many families travelling to various tourist destinations. This phenomenon is interesting to be investigated. Existing research results can be utilized by stakeholders to develop their own policies and strategies. However, at this time not much study exists in family travel. This study  examines family’s travel motivations, family’s activities in destination, and the differences of family’s activity choice across categories of travel motivations. Survey method has been employed in this study. The sample was obtained from a residence in Bogor City, West Java and consisted of 300 families chosen by convenience sampling technique. Data were analyzed using descriptive analysis and hypothesis test using chi-square. The findings indicated that there were two dominant family’s travel motivations, personal escape and interpersonal seeking. The family chose natural, cultural, and special tourist activities. Family’s activity choice across categories of travel motivations was the same except rafting. It was most preferred by families who had personal escape motivation.